Nonlinear Cointegration and Asymmetric Adjustment in Purchasing Power Parity of the USA, Germany, and Pakistan - Kashif Ali; Hafsa Hina; Muhammad Ijaz; Mahmoud El-Morshedy (Complexity)
The current study explores nonlinear cointegration as well as asymmetric adjustment to investigate the long-run purchasing power parity in three major trading partners of Pakistan. The ESTAR and LSTAR models were used to investigate the behavior of the nominal exchange rates. The findings declared that series follows the nonlinear exchange rate. The asymmetric behavior of the exchange rate allows the threshold cointegration model to be implemented. In the case of Pakistan-China, the result suggests that long-run PPP holds. As a result, trading will be more profitable if the exchange rate is varied in relation to major trading partners rather than just the US dollar.